U.S.-Cuba Normalization: U.S. Constituencies for Change - Ted Piccone (IdeAs)
The United States and Cuba made important strides after the re-launch of diplomatic relations between the two countries under Presidents Barack Obama and Raul Castro in 2015-2016. These changes were both psychological and symbolic as key themes of mutual respect, sovereignty and reconciliation gained ground. They were also pragmatic, cutting across a wide range of issues from travel and hospitality, which has helped catalyze a major increase in U.S. travelers to the island, to telecommunications and migration. These measures reflected the emergence of an effective coalition of U.S. constituencies that organized individual and joint efforts to regain the advantage over the traditional pro-embargo approach of the Cuban diaspora.With the inauguration of Donald Trump in January 2017, however, forward momentum in bilateral relations has nearly ground to a halt as the hardline Cuban exile community has reasserted primacy in shaping U.S. policy toward the island. Nonetheless, the Republican Party is divided over how far to roll back the changes made by Obama as specific constituencies with the most to gain from normalization defend their interests in continued normalization. The author analyzes the various U.S. stakeholders pushing for relaxation of the embargo and how the Obama administration’s policies benefited them. It will also look at the role of the U.S. Congress and the prospects for rapprochement in the years ahead.